Proton pump inhibitors overuse - consequences among patients - Patrycja Kmiotek; Andrzej Materniak; Barbara Skrzydło-Radomańska (Kazimierz Wielki University, 2019)
Introduction Omeprazole was first proton pump inhibitor (PPI) approved for use by patients. Thirty years have passed since then. Due to their effectiveness, low price and safety proton pump inhibitors have become one of the most frequently prescribed medicines in the world. In recent years, more attention has been paid to the problem of their overuse. Aim of the study The aim of our study was to investigate the scale of proton pump inhibitors overprescription and possible resulting side effects. State of knowledge Analyzed observational studies proves that problem is present both in hospitals and ambulatory clinics. Research shows increasingly frequent use of this medicines in case of non-specific abdominal discomfort or in many cases without any indications. This results in prolonged and unnecessary therapy. The possibility of obtaining medicines over the counter and patients non-compliance, are also a challenge in maintaining high-quality therapy. In many cases patients taking drugs irregularly or do not stop therapy, even being free from symptoms. Conclusions Despite the fact that proton pump inhibitors are considered safe drugs, more attention should be paid to the compatibility of their use with recommendations. There are also evidences about the possibility of side effects associated with long-term proton pump inhibitor therapy, which can be particularly dangerous for older patients with multiple diseases. It is necessary to inform patients about the need of discontinuation therapy in case of recovery, which will reduce the risk of adverse effects.